Fatigue resistance is altered during the high-hormone phase of eumenorrheic females but not oral contraceptive users - Lee, S. J.; Sim, M.; Van Rens, F. E.; Peiffer, J. J. (Medicine & Science in Sports & Exercise, 2024)
Purpose This study aimed to examine the effect of ovarian hormones and their synthetic equivalents on substrate utilization and fatigue resistance during a race-specific cycling protocol.